Control of hypertension in elderly patients with felodipine and metoprolol: a double-blind, placebo-controlled clinical trial. - Freeling, P (1987)
1. Forty-nine patients aged 65-80 years, whose Phase V diastolic blood pressure (dBP) was above 95 mmHg after 4 weeks open treatment with metoprolol 50 mg twice daily were randomized to receive, double-blind, the calcium antagonist felodipine (n = 32) 2.5 mg twice daily or placebo (n = 17) in addition to metoprolol for 2 weeks. If the dBP remained greater than 95 mmHg, the dose of felodipine or placebo was doubled for a further 2 weeks; if the dBP was still greater than 95 mmHg, the dose of felodipine was doubled again to 10 mg twice daily or the corresponding placebo dose given. The duration of the double-blind period was 6 weeks, all patients receiving metoprolol 50 mg twice daily throughout. 2. At the end of the double-blind period, the seated dBP was reduced from 103 +/- 5 (mean +/- s.d.) to 88 +/- 7 mmHg (P less than 0.001) by felodipine and from 105 +/- 100 +/- 11 mmHg (NS) by placebo. The differences between these reductions (P less than 0.01) and between the final dBPs (P less than 0.001) were significant. Eighty-nine per cent of patients receiving felodipine and 33% of those receiving placebo (P less than 0.001) had controlled (dBP less than or equal to 95 mmHg) BPs. Half (14/27 completing) of the patients receiving felodipine required 2.5 mg throughout; 9/27 needed 5 mg and 4/27 10 mg twice daily. Adverse events occurred with equal frequency in the two groups, but the profile was different.(ABSTRACT TRUNCATED AT 250 WORDS)